On Some Coincidence Best Proximity Point Results. (22nd December 2021) - Saleem, Naeem; Ahmad, Haroon; Aydi, Hassen; Ulrich Gaba, Yaé
Abstract : In this paper, we discuss some (coincidence) best proximity point results for generalized proximal contractions and λ − μ -proximal Geraghty contractions in controlled metric type spaces. To clarify our study, various examples are given and some conclusions are drawn.